Peran Guru Bimbingan dan Konseling pada Sekolah Penyelenggara Pendidikan Inklusi - Lattu, Desje (Jurnal Bimbingan dan Konseling Terapan, 2018)
The development of contemporary education leads to the model of inclusive education. Almost all developed countries have appreciated, treated and respected children with special needs more detailed and very human. In the United States, for example, inclusive education is growing very rapidly in the presence of various elements of mutual support. In addition, in Japan children with special needs and parents are given the freedom to choose the school according to the wishes of children with special needs. Schools that receive special needs children provide educational services according to their specificity. Inclusive education is now beginning to be developed in Indonesia, with various areas being supported by the goal of implementing inclusive education.